Religious Moderation Policy Through Good Governance and Bugis Philosophy Pakkawarui Madecengnge - Syafa’at Anugrah Pradana; Hasanuddin Hasim; Yusniar (Jurnal Mulawarman Law Review, 2026)
This article examines the strengthening of religious moderation policy in Amparita Village, South Sulawesi, by integrating the General Principles of Good Governance (AUPB) with the Bugis local philosophy Pakkawarui Madecengnge (“keep doing goodness”). The study is motivated by the increasing challenges of religious diversity and the need for a governance-based framework to ensure sustainable harmony. The objective of this paper is to analyze how good governance principles—such as legal certainty, transparency, accountability, and public participation—intersect with Bugis cultural values in shaping inclusive religious moderation policies at the local level. Employing a juridical-empirical method with qualitative analysis, data were collected through in-depth interviews with local government officials, religious leaders, and community representatives, supported by document analysis of relevant regulations. The findings reveal that the implementation of religious moderation in Amparita is not merely a top-down policy but is rooted in everyday social practices and cultural ethos. The philosophy of Pakkawarui Madecengnge provides an ethical foundation that resonates with AUPB, reinforcing collective responsibility, fairness, and transparency in policy implementation. Results also highlight several challenges, including the absence of binding local regulations, limited financial resources, and reliance on the initiative of local leaders. Nevertheless, the integration of AUPB and local wisdom has fostered effective interfaith dialogue, strengthened social cohesion, and enhanced public trust in governance. This study concludes that combining formal governance principles with local cultural values offers a replicable model for religious moderation policy in plural societies. The contribution of this article lies in positioning religious moderation not only as a socio-cultural practice but also as a governance-based public policy framework enriched by local wisdom.